Issues of the legal classification in cases of death by firearm or highly active poisonous substance - Pandilova, Nadya (Law Journal of New Bulgarian University, 2022)
This article addresses the issue of the distinguishing criterion between the constituent elements of the simple (Art. 122, para 2 CC) and professional negligence (Art. 123, para 1 CC) in cases where death is caused by a firearm or a highly active poisonous substance. It is concluded that, in order to distinguish between the constituent elements of the abovementioned crimes, it is necessary for the law enforcement authorities to assess the nature of the causative activity itself.